Um estudo da mobilidade acadêmica internacional em cursos de graduação da Universidade Federal de São Carlos no âmbito dos programas AUGM, BRACOL, BRAMEX e acordos bilaterais de cooperação - Forim, Andréia Businaro (2020)
The internationalization of higher education institutions is an increasingly recurrent theme in the context of academic discussions because, in addition to being an impacting force in higher education, it is one of the most important challenges facing the 21st century. International academic mobility, a phenomenon that moves a significant number of students across borders, is the most visible face of the Internationalization of Higher Education. The activities associated with internationalization go far beyond the cross-border mobility of students, as it also encompasses curriculum development, international cooperation, staff development, among other aspects. In this scenario, this research aimed to assess international academic mobility in undergraduate courses at the Federal University of São Carlos, within the framework of the programs AUGM, Bracol, Bramex and bilateral cooperation agreements, from 2016 to 2019. Academic mobility international is one of the most successful mechanisms in preparing students to work and live in a globalized world, as well as in the acquisition or consolidation of transversal skills such as foreign language skills, independence, initiative, flexibility, intercultural understanding, sensitivity understanding, beyond international awareness. The present research adopted the survey methodology. It has a quantitative approach, and based on the objectives is descriptive. Data collection was carried out through documentary research and the application of a questionnaire to undergraduate students who participated in international academic mobility in the period from 2016 to 2019. The results obtained were analyzed and discussed based on the proposed objectives, confronting them with the literature. The analysis of the results was made through the Average Ranking (RM) of the Likert items within each category. Among the results of this study, it can be inferred that although the international academic mobility at UFSCar is expanding, from the weak spots detected through the questionnaire, it is possible to implement improvement actions to increase the number of academic mobility incoming and outgoing. It was also found that Latin America has developed its international academic mobility, notably through AUGM, however, it still needs to be improved, aiming to attract students from all areas of knowledge. The study also sought to offer subsidies for several institutional actions through the indicators presented. Limitations and suggestions for future studies are presented in the final considerations.